Central clearing and CDS market quality - Silva, Paulo (2019)
This paper contributes to the literature on the impact of central clearing on financial market quality. Focusing on the CDS market, a difference-in-differences analysis is performed to identify effects of voluntary central clearing of contracts on ICECC and ICECE. Patterns of market quality proxies are compared before and after central clearing initiation. We conclude that central clearing improves liquidity, price informativeness and precision, and also the integration of the CDS and stock markets. Results are inconclusive for the impact on CDS price volatility.